2004
DOI: 10.1002/jssc.200401827
|View full text |Cite
|
Sign up to set email alerts
|

Applications of silica‐based monolithic HPLC columns

Abstract: The recent invention and successive commercial introduction of monolithic silica columns has motivated many scientists from both academia and industry to study their use in HPLC. The first paper on monolithic silica columns appeared in 1996. Currently about 200 papers have been published relating to applications and characterization of monolithic silica columns, including monolithic capillaries. This review attempts to give an overview covering various aspects of this new column type in the field of high throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
237
0
9

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 398 publications
(251 citation statements)
references
References 88 publications
5
237
0
9
Order By: Relevance
“…modification of silica monolithic columns have been extensively One of the recent solutions for high speed separation is the studied, and their users are increasingly widespread. [19][20][21][22] On the ultrahigh pressure liquid chromatography (UPLC). 5,6 In the other hand, polymer-based monolithic columns have unique UPLC, a column packed with micro particles less than 3 μm in advantages such as an availability over a wide pH range and size is used, since the column efficiency increases with simplicity of preparation.…”
Section: Introductionmentioning
confidence: 99%
“…modification of silica monolithic columns have been extensively One of the recent solutions for high speed separation is the studied, and their users are increasingly widespread. [19][20][21][22] On the ultrahigh pressure liquid chromatography (UPLC). 5,6 In the other hand, polymer-based monolithic columns have unique UPLC, a column packed with micro particles less than 3 μm in advantages such as an availability over a wide pH range and size is used, since the column efficiency increases with simplicity of preparation.…”
Section: Introductionmentioning
confidence: 99%
“…It generates a very low backpressure (equivalent to that of a column packed with 11 lm particles) in conjunction with high chromatographic performance (equivalent to a column packed with 3-3.5 lm particles). 13 For instance, Chankvetadze et al 14 described the baseline enantioseparation of 2,2,2-trifluoro-1-(9-anthryl)ethanol in about 30 sec on a monolithic silica column coated with cellulose tris(3,5-dimethylphenylcarbamate). Lubda et al 15 also reported the fast enantioseparation of several drugs on a monolithic silica column with chemically bonded b-CD.…”
Section: 2mentioning
confidence: 99%
“…[1][2][3][4][5] Materials suitable for the fabrication of the monolithic bed are divided into two main categories: silica [6][7][8] and polymer [9][10][11][12][13][14][15][16] monolith. Silica monolithic columns have well-controlled pore structure, good mechanical strength, and high column efficiency, 7,8 while polymer monolithic columns have unique features such as applicability over a wide pH range and simplicity of preparation. [12][13][14][15][16] One of the most attractive properties of monolithic columns is their low flow resistance resulting from the high permeability of monolithic beds.…”
Section: Introductionmentioning
confidence: 99%